Advances in test and measurement of the interface adhesion and bond strengths in coating-substrate systems, emphasising blister and bulk techniques. (June 2019) - Chen, Xiaomei; Shaw, Christopher; Gelman, Len; Grattan, Kenneth T.V.
Abstract: In this paper, recent advances in the minimum-destructive testing of the adhesion of coating-substrate systems are reviewed, focusing on key techniques such as micro- and nano-scale levels of indentation, scratching, laser-induced wave shock, as well as the blister and buckle approach. Along with adhesion failure tests, the latest and most extensive applications of the adhesion test methods in nano-, micro- and bulk-coating technology and the associated techniques to determine the minimum damage defects left on the coatings are discussed and their use reviewed.